Discovery of Risdiplam, a Selective Survival of Motor Neuron‑2 (SMN2) Gene Splicing Modifier for the Treatment of Spinal Muscular Atrophy (SMA) - Ratni, Hasane; Ebeling, Martin; Baird, John; Bendels, Stefanie; Bylund, Johan; Chen, Karen S; Denk, Nora; Feng, Zhihua; Green, Luke; Guerard, Melanie; Jablonski, Philippe; Jacobsen, Bjoern; et al. (Journal of medicinal chemistry, 2018)
SMA is an inherited disease that leads to loss of motor function and ambulation and a reduced life expectancy. We have been working to develop orally administrated, systemically distributed small molecules to increase levels of functional SMN protein. Compound 2 was the first SMN2 splicing modifier tested in clinical trials in healthy volunteers and SMA patients. It was safe and well tolerated and increased SMN protein levels up to 2-fold in patients. Nevertheless, its development was stopped as a precautionary measure because retinal toxicity was observed in cynomolgus monkeys after chronic daily oral dosing (39 weeks) at exposures in excess of those investigated in patients. Herein, we describe the discovery of 1 (risdiplam, RG7916, RO7034067) that focused on thorough pharmacology, DMPK and safety characterization and optimization. This compound is undergoing pivotal clinical trials and is a promising medicine for the treatment of patients in all ages and stages with SMA.